Application of eligibility criteria from DAPA-HF, EMPEROR-Reduced, and PARADIGM-HF trials to a population with heart failure with reduced ejection fraction at a specialized cardiology Clinic in Medellin, Colombia: A Retrospective Cohort Study (2023)
ABSTRACT: Introduction: The evidence for the pharmacological treatment of heart failure is based on randomized clinical trials with strict inclusion and exclusion criteria. Objectives: To evaluate the proportion of patients with chronic heart failure from an outpatient cohort who would be eligible for the trials DAPA-HF, EMPEROR-reduced, and PARADIGM-HF, and to determine potential differences between study populations. Methods: Through revision of medical records, we calculated the proportion of patients who would have been eligible for each study and evaluated the incidence of heart failure hospitalizations and all-cause mortality during this period. Results: A total of 446 patients were included in the cohort. Approximately 75% would be ineligible for the trials, mainly because of their comorbidities. Ineligible patients had a higher all-cause mortality, but a similar incidence of hospitalization. Conclusion: Approximately 1 in 4 patients from a heart failure clinic in Medellin, Colombia would meet the eligibility criteria for the DAPA-HF, EMPEROR-reduced, and PARADIGM-HF trials. These findings highlight the need to complement randomized clinical trials with real-world data.